Bridging Therapy for Acute Stroke as the Initial Manifestation of Takayasu Arteritis: A Case Report and Review of Literature - Dai, Yongqiang; Zhong, Yi; Jian, Banghao; Liu, Ping; Song, Kangyu; Li, Yu; Wu, Aimin; Zhang, Bingjun (Frontiers in Immunology, 2021)
Takayasu arteritis (TA) is a chronic inflammatory disease involving the aorta and its principal branches. Acute ischaemic stroke (AIS) as the initial manifestation of TA is uncommon. There is little evidence on the efficacy of bridging therapy for AIS induced by TA. A 23-year-old Chinese woman with a suspected stroke presented to our hospital with sudden onset of right-sided weakness, right facial palsy, and aphasia that occurred 1 hour ago. After physical and ancillary examinations, recombinant tissue plasminogen activator was administered to the patient, which led to partial recovery. Her neurological function deteriorated with a large salvageable ischaemic penumbra on computed tomography perfusion. Cerebrovascular angiography showed multiple stenoses in the brachiocephalic trunk, the beginning of the right common carotid artery (CCA), and the bilateral subclavian arteries, as well as occlusion of the left CCA and its branches. Mechanical thrombectomy of the left middle cerebral artery was performed immediately. Percutaneous transluminal balloon angioplasty of the left CCA followed by stent implantation of the proximal left CCA was then performed. A diagnosis of TA was made based on the findings. The patient’s neurological deficit fully recovered with immunosuppressants at the 3 month-follow-up. We report a rare case of a patient with TA initially presenting with AIS treated with bridging therapy with full recovery of neurological function. Bridging therapy should be taken into consideration for AIS in patients with TA. Further study is needed in this regard.